2020
DOI: 10.22541/au.159708697.70680949
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is Mean Platelet Volume a Predictive Marker for the Diagnosis of COVID-19 in Children?

Abstract: Aim: To investigate the mean thrombocyte volume (MPV) in asymptomatic children infected with COVID-19. Methods: The study included 55 children infected with COVID-19 and 60 healthy children for the comparison of leukocyte and thrombocyte count, MPV, and serum C-reactive protein (CRP) levels. Demographic data and clinical findings of all the cases were recorded, including age, gender, weight, temperature, cough, shortness of breath and contact history. Results: The MPV values were determined to be statistically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
2
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 8 publications
2
2
0
1
Order By: Relevance
“…In this study, While ROC Curve analysis of lymphocyte count did not give significant results, the area under the curve of the MPV was below 0.40, and it was found that CRP (0.74) and LDH (0.70) have highest area under the curve (Table 3; Figure ). While Gumus et al (17) stated that there was a difference in the MPV and lymphocyte count values between the patient and control groups, Seyit et al (18) showed that the sensitivity of LDH and CRP was 60% and 66%, respectively, and similar to the results of our study, they found that there was no difference between the patient and control groups in the MPV. Due to the different results in the literature, regression modeling was performed to include more than one parameter in this study (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…In this study, While ROC Curve analysis of lymphocyte count did not give significant results, the area under the curve of the MPV was below 0.40, and it was found that CRP (0.74) and LDH (0.70) have highest area under the curve (Table 3; Figure ). While Gumus et al (17) stated that there was a difference in the MPV and lymphocyte count values between the patient and control groups, Seyit et al (18) showed that the sensitivity of LDH and CRP was 60% and 66%, respectively, and similar to the results of our study, they found that there was no difference between the patient and control groups in the MPV. Due to the different results in the literature, regression modeling was performed to include more than one parameter in this study (Table 4).…”
Section: Resultssupporting
confidence: 89%
“…In a study recently reported from Turkey, a group of COVID-19 patients were compared with a healthy population in the pediatric age group. It has been emphasized that those with COVID-19 have higher MPV and lower lymphocyte values compared to the healthy group (21). In our study, MPV was found to be significant in predicting the ICU requirement.…”
Section: Resultssupporting
confidence: 46%
“…Thrombocytes play a role in the pathogenesis of infectious diseases. Previous studies have suggested that megakaryocytes may be affected by cytokines such as IL-3, IL-6, and lead to more reactive production of thrombocytes (32). Therefore, MPVLR is expected to be higher in severe inflammation.…”
Section: �Correlation Between Mean Platelet Volume and Other Laborato...mentioning
confidence: 98%